A Model in Female Rats With Phenotypic Features Similar to Interstitial Cystitis/Bladder Pain Syndrome - Ness, Timothy J.; DeWitte, Cary; DeBerry, Jennifer J.; Hart, Morgan P.; Clodfelder-Miller, Buffie; Gu, Jianguo G.; Ling, Jennifer; Randich, Alan (Frontiers in Pain Research, 2021)
This report describes methodological and exploratory investigations of the zymosan-induced neonatal bladder inflammation (NBI) model of interstitial cystitis/bladder pain syndrome (IC/BPS) in female rats. These results validate and extend the currently employed model by evaluating critical timepoints for obtaining treatment effects and identified that a second insult as an adult including repeat intravesical zymosan, intravesical lipopolysaccharide, acute footshock stress, neuropathic nociception (facial) or somatic inflammation (hindpaw) all resulted in magnified visceromotor responses to urinary bladder distension (UBD) in rats which had experienced NBI when compared with their controls. NBI also resulted in increased tone and reactivity of pelvic floor musculature to UBD, as well as increased responsiveness to intravesical potassium chloride solutions, abnormal anxiety measures (elevated plus maze) and an increased number of submucosal petechial hemorrhages following 30 min of hydrodistension of the bladder. These phenotypic findings have correlates to the clinical features of IC/BPS in humans and so support use of this model system to examine mechanisms of and treatments for IC/BPS.